Strategy for Achieving Production Target in Bakery Sejahtera Using the Fishbone Diagram - Budiman, Sri Anggraeni; Mela, Ervina (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2025)
The failure to achieve production targets has become the main challenge for UMKM Bakery Sejahtera in Sumedang Regency. This issue has the potential to reduce customer satisfaction and market trust. This study aims to analyze the factors contributing to this issue using a qualitative approach through interviews and observations. Data were analyzed using a Fishbone Diagram to identify root causes across six main aspects: manpower, methods, materials, machinery, measurement, and mother nature (enviroment). The findings indicate that a shortage of labor, limited machine capacity, delays and improper storage of raw materials, the absence of Standard Operating Procedures (SOPs), and environmental factors such as high room temperature and frequent power outages are the dominant causes. Recommendations include workforce addition, implementing more effective task distribution, adding one oven and one mixer of similar capacity, improving supplier relationships and diversifying sources, developing and applying clear SOPs for each production stage, introducing a more structured production monitoring and measurement system, and enhancing the working environment by improving ventilation, maintaining cleanliness, and preparing contingency plans for power outages.